ANALISIS KINERJA PENGELOLAAN ZAKAT DI BADAN AMIL ZAKAT NASIONAL (BAZNAS) KOTA YOGYAKARTA - M Samsul Haidir (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri (UIN), 2020)
AbstractZakat is a means of worship that must be fulfilled by Muslims, where it involves a servant's horizontal relationship with God. The realization of the collection of zakat and infaq by BAZNAS in Yogyakarta in 2016 reached 4.38 billion rupiah. As for the purpose of this study is to evaluate the performance of the government and society in managing zakat, the performance of zakat institutions, and the influence of zakat on the welfare of those who have the right to receive zakat in Yogyakarta. This research was conducted using survey methods through interviews using questionnaires. Samples were selected using purposive sampling technique. The analysis was carried out using the National Zakat Index using the Mixed Method. The results showed that the performance of zakat management in Yogyakarta was quite good with an index value of 0.4878.